From skin to mind: the psychological consequences of psoriasis severity and approaches to coping - Kapur, Sahil; Shah, Sajan; Reddy, Akshay; Sidhu, Kermanjot; Kapur, Kabir D.; Satya-Akunuri Koka, Sanjay; Houdi, Mark; Burkhart, Craig G. (International Journal of Research in Dermatology, 2025)
Psoriasis is a chronic, systemic, inflammatory skin condition that causes red, scaly, and pruritic lesions. Psoriasis can be detrimental to both physical and mental health. The worsening of psoriasis is caused by mental stress, especially depression and anxiety. Approximately 34% of patients with psoriasis exhibit signs of anxiety. Symptoms of anxiety are present in about 34% of patients with psoriasis. Studies reveal that 15% of patients meet the diagnosis for social anxiety disorder, 11% for generalized anxiety disorder, and 9% for unspecified anxiety disorder. Higher rates of depression and anxiety are observed among patients with severe psoriasis compared to those with less severe psoriasis. Psychosocial distress and higher levels of anxiety and depression scores are noted in women and younger patients. The Salford psoriasis index (SPI) and dermatology quality of life index (DQL) are good measures to evaluate the severity of the disease and quality of life (QoL), respectively. Both these indices confirm an inverse relationship between the severity of psoriasis and a decrease in mental health. Psoriasis requires a multidisciplinary plan to treat both psoriasis and the associated mental health conditions. There is evidence-based data for the effectiveness of cognitive-behavioral therapy (CBT) and mindfulness-based therapies in the treatment of psoriasis patients. Having a comprehensive treatment approach to treat psoriasis and mental illness simultaneously may lead to improved patient outcomes and QoL.